A ProperFit Virtual Machine Migration Approach for the Load Balancing in Cloud - Tiwari, Damodar; Singh, Shailendra; Sharma, Sanjeev (International Journal of Computer Sciences and Engineering, 2018)
With the invention of the cloud computing, the utilization of the physical resources has improved drastically. The main technology that enable the cloud computing is virtualization which allows to create several virtual machine (VM)onto the single physical machine (PM). It increased the utilization of the physical resources because single hardware resources are shared by the several users. Although virtualization technique optimize the server utilization but add new issue named load balancing that need to addressed for the effective utilization of the physical resource and maintain the quality of services (QoS). To deal with the load balancing VM migration approach is used which permit to travel the VM from physical machine (host) to another. Three stages are engaged with the relocation procedure i.e., source PM choice, VM selection and the last step is target PM selection. Plenty of work on the load balancing in cloud are presented in the last few decades and mostly they are differ in the VM selection and VM placement polices. After the study of previous work on the VM migration it can be says that choosing an appropriate VM is a non-trival task and the performance of the load balancing approach is mainly depends on the appropriate VM selection polices. In this paper we select the three different types of virtual machine for the migration and then placed it to the physical machine where the load on the physical machine is between 20 to 50. CloudSim simulator is used to evaluate the performance of the physical.